2004
DOI: 10.2460/javma.2004.224.1808
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of thoracolumbar intervertebral disk extrusion in chondrodystrophic dogs after surgical decompression with or without prophylactic fenestration: 265 cases (1995–1999)

Abstract: Prophylactic fenestration is generally successful in preventing future disk extrusions at fenestrated disk spaces. Prospective evaluation is still required to determine whether fenestration decreases the overall rate of recurrence. Prophylactic fenestration could promote disk extrusion at adjacent, nonfenestrated disk spaces. This could have a substantial clinical impact if recurrence develops at L4-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
169
5
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(192 citation statements)
references
References 26 publications
12
169
5
6
Order By: Relevance
“…In this study, the breeds most commonly suffering TL-IVDH were the Dachshund (53.3%) followed by the Beagle (13.3%). Similar results have been reported previously, showing that the Dachshund and Beagle were the breeds most commonly presenting TL-IVDH, accounting for 34.7% to 65.7% and 2.9% to 10.9% of cases, respectively [2,3,10,12,14,16,17,19,[21][22][23]. Our data from Japan concerning the susceptibilities of other pure breeds is closely similar to previous reports from the U.S.A. Age at admission in this study agreed with previous data that indicated 5.1 to 6.5 years of age [7, 9, 15-17, 19, 21, 23, 25, 26].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the breeds most commonly suffering TL-IVDH were the Dachshund (53.3%) followed by the Beagle (13.3%). Similar results have been reported previously, showing that the Dachshund and Beagle were the breeds most commonly presenting TL-IVDH, accounting for 34.7% to 65.7% and 2.9% to 10.9% of cases, respectively [2,3,10,12,14,16,17,19,[21][22][23]. Our data from Japan concerning the susceptibilities of other pure breeds is closely similar to previous reports from the U.S.A. Age at admission in this study agreed with previous data that indicated 5.1 to 6.5 years of age [7, 9, 15-17, 19, 21, 23, 25, 26].…”
Section: Discussionsupporting
confidence: 79%
“…For instance, 22/23 (96%) of L4‐S3 SCI small‐breed or chondrodystrophic dogs with compressive lesions and UMN incontinence recovered within 3 weeks, and the remaining dog had recovered by 40 days. This result is not surprising, because these dogs are analogous to small‐breed, chondrodystrophic dogs with T3‐L3 SCI and preserved CPP caused by intervertebral disk extrusions, and a consensus exists that these dogs have an excellent prognosis (86%‐96% recovery rate) after decompressive surgery 5, 15, 17, 18, 19…”
Section: Discussionmentioning
confidence: 88%
“…One of these studies concerned dogs with loss of CPP,4 but the other 2 studies only had 15 and 36 such dogs. Prognosis for dogs with retained CPP in thoracolumbar intervertebral disk herniation usually is considered excellent (functional recovery in approximately 95% of dogs overall5, 15, 17, 18, 19), and thus, the low number of dogs that did not recover in these studies (0/175 and 7/366) is not surprising and may have led to a type II error.…”
Section: Discussionmentioning
confidence: 93%
“…Chondrodystrophic breeds such as Dachshunds are frequently affected by early degeneration of intervertebral disks and presence of intercapital ligaments may partially prevent intervertebral disks to herniate in cranial segments of the thoracic vertebral column 2, 3, 4, 5, 23, 42, 44, 45…”
Section: Discussionmentioning
confidence: 99%